Insights on dying, dementia and death certificates - Sofie Vandormael; Alexander Meirschaert; Jan Steyaert; Jan De Lepeleire (BMC, 2018)
Abstract For our master thesis in medicine, we aimed to determine how many deaths were caused by and with dementia in 2014 and we compared our results with figures from abroad. The mortality rates of 2014 in Flanders were used to determine the amount of deaths related to dementia. These figures are collected by Vlaams Agentschap Zorg & Gezondheid (VAZG) and coded per ICD-10 classification. Of all deaths in Flanders in 2014, 6.60% were caused by dementia and 4.29% were caused by another condition, while also suffering from dementia. Data from abroad are ambiguous. While working on our thesis about "death & dementia", we questioned the reliability of mortality statistics. Possible explanations could be; the complexity of completing death certificates correctly and the challenges involved in properly constructing a chain of causes of death. The accuracy of mortality data can be improved by training and redrafting death certificates.